2019
DOI: 10.1177/0308518x19865550
|View full text |Cite
|
Sign up to set email alerts
|

Learning through urban labour pools: Collected worker experiences and innovation in services

Abstract: Knowledge-intensive services firms (KIS) depend on the skills and networks of employees, and tend to cluster in large-city regions. This raises the fundamental question of whether KIS 'learn through urban labour pools' in manners that have implications for innovation. To address it, a distinction is in this paper made between 'related variety' (RV) and 'unrelated variety' (URV) of work-life experiences collected by employees and combined in firms. The empirical analysis uses innovation survey and register data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 81 publications
0
9
0
Order By: Relevance
“…also Firgo & Mayerhofer, 2018). In line with this, Herstad et al (2019) found KIS benefitting for product innovation from combining a broad range of experience‐knowledge drawn specifically from the labour markets of large cities. This is consistent with the notion that innovation in the rapidly changing market environments of services demand bridging of different cognitive domains (Bugge, 2011; Jøranli, 2018; Pershina et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 82%
See 3 more Smart Citations
“…also Firgo & Mayerhofer, 2018). In line with this, Herstad et al (2019) found KIS benefitting for product innovation from combining a broad range of experience‐knowledge drawn specifically from the labour markets of large cities. This is consistent with the notion that innovation in the rapidly changing market environments of services demand bridging of different cognitive domains (Bugge, 2011; Jøranli, 2018; Pershina et al, 2019).…”
Section: Conceptual Frameworkmentioning
confidence: 82%
“…Given that non-conventional location choices suggest different business strategies and innovation models (e.g. Shearmur, 2015;Herstad et al, 2019), KIS located outside these urban labour market regions are excluded from the analysis.…”
Section: Methodological Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…This and vibrant labour markets is generally said to give enhanced access to knowledge spillovers (Fitjar & Rodríguez-Pose, 2020). Cities are also primary sites for knowledge-intensive services (Herstad et al, 2019). Market niches combined with variety of resources and connectivity through networks might give rise to firm-level heterogeneity (Eriksson & Lengyel, 2019).…”
Section: Lesson For Our Approachmentioning
confidence: 99%